Development of Student’s Worksheet using Project-Based Learning (PjBL) on Ecosystem Concept for Class X SMA - Riana, Febi; Sunarto, Sunarto; Mamangkey, Jendri (Universitas Islam Negeri Walisongo Semarang, 2024)
The students' learning interest is decreasing due to the lack of interactive, enjoyable, and supportive instructional materials to help them achieve good learning outcomes. Therefore, researchers innovated by developing Learner Worksheets (LKPD) based on Project-Based Learning (PjBL). The research aims to assess the feasibility of PjBL-based LKPD through evaluations from experts (in content, media, and language) and students' responses. The research type used is Research and Development (R&D). The assessment results from content experts showed a score of 82.03%